IMPLEMENTING LEARNING SUPERVISION IN THE INDEPENDENT LEARNING CURRICULUM - Sanasintani; Mira Mirnawati (European Journal of Humanities and Educational Advancements, 2024)
Activity supervision is inspection, examination, supervision or surveillance. In context school as organization education, supervision constitute part from administrative and management processes. Activities supervision complete functions administration at the school as function last, that is evaluation to all activity in reach objective. With supervision, will give inspiration For together finish jobs with amount more a lot of time more fast, way more easy, and more results Good than If done Alone. Supervision have role optimizing not quite enough answer from all programs. Supervision concerned disconnected with all effort research aimed at all aspects that are determining factors success. With know condition aspects the in a way detailed and accurate, can is known with exactly what is needed For increase quality the organization concerned.